The Use of the "Box- Jenkins" Methodology to Forecast the Time Series for Gross Fixed Capital Formation – An Applied Study on the Saudi Arabia Kingdom – - Abdelgadir, Gariballa Abdelmageed (Journal of Economic, Administrative and Legal Sciences, 2022)
The study aimed to analyze the current and future behavior of the time series of Gross fixed Capital Formation in the Kingdom of Saudi Arabia. Data of the study for the period from 1968 to 2019 was collected from the website of the World Bank: https://data.albankaldawli.org/. The study found, through the use of Stationary tests, that the time series under study were not stationary in their level, but became stationary after putting it in the form of the first differences, the study was adopted on the application of the Box- Jenkins methodology for prediction and time series analysis. It found that, the best model fits the data of the Gross Fixed Capital Formation series is the ARIMA model (2,1,4). This model was used to forecast the future for the years from 2020 to 2023 AD. The forecast results in Saudi Arabia kingdom showed that the Grand total of the expected fixed capital formation will range between approximately (19.6- 29.4) billion riyals during the forecast period, and that the Total Fixed Capital Formation in the Kingdom of Saudi Arabia is taking an upward trend during the forecast period (2020- 2023). Finally, the study reached some recommendations, the most important of which is to take advantage of the study results to predict the Total Fixed Capital Formation for the coming years, and to conduct other predictive studies for some important economic indicators, such as the Gross Domestic Product and Foreign Direct Investment.
Keywords: Time Series; Stationary; Gross fixed Capital Formation; Box- Jenkins; Forecast